Study on the Bottom Diversion Outlets of the Three Gorges Project - TANG Li (Renmin Zhujiang)
Construction of the Three Gorges Project is divided into three stages. The second stage is to close the left bank main riverbed, divert the stream to the right bank open channd and build the spillway section in the mian river bed and the powerhouse on theleft bank. The spillway section will be provided with three rows of release outlets of which 22 bottom outlets will be used for construction diversion in the third stage, hence, it is an important structure for ensuring the safety in the construction of of the right bank powerhouse in the third stage and the safety in the operation of the left bank powerhouse.